Impact of Mergers and Acquisitions on European Insurers: Evidence from Equity Markets - Petr Jakubik; Dimitris Zafeiris (Charles University in Prague, Institute of Economic Studies (IES), 2016)
The current macro-economic and financial conditions remain extremely challenging for the European insurance sector. Under the ongoing low yield environment insurers are changing their business models and looking for new investment and business opportunities to improve their profitability and the overall solvency positions. This is also reflected in an increasing interest in mergers and acquisitions to achieve sufficient returns. However, there is no clear answer in the literature whether this strategy brings the expected positive results. This study empirically tests the effects of mergers and acquisitions (M&A) on share prices of European insurers via an event study. Our results do not confirm the positive impact of such strategies on acquirers' share prices delivering abnormal returns for shareholders.
Keywords: 330; Übernahme; Ankündigungseffekt; Kapitalmarktrendite; Versicherung; Europa